Microstructure and Mechanical Properties of High-Carbon-Containing Fe-Ni-Mn-Al-Cr High-Entropy Alloy: Effect of Thermomechanical Treatment - Mohanty, S.; Kothari, A.; Raghavan, R.; Sahu, V. K.; Gurao, N. P.; Sahu, K. K.; Dhindaw, B. K.; Zeng, L.; Xia, M.; Gollapudi, S. (Frontiers in Materials, 2022)
The effect of heat treatment on the mechanical properties of two high carbon containing (1.5 and 3 at. %) single phase fcc Fe40.4Ni11.3Mn34.8Al7.5Cr6 high entropy alloy is reported in this study. In the cold rolled condition, the 1.5 at.% and 3 at.% C containing alloys, referred to as CR1 and CR2 respectively, demonstrated yield strength values of 1423 and 1197 MPa respectively. The corresponding values of elongation to failure was noted to be 4.05 and 4.46 % respectively. Upon heat treatment at 1050 °C, the CR1 and CR2 samples, referred to as HT1 and HT2 in the heat-treated condition, demonstrated yield strength values of 358 and 327 MPa respectively. The elongation to failure of HT1 and HT2 was found to be 37.2 and 26.4% respectively. The change in mechanical properties brought about by heat treatment was understood by studying the phase composition, microstructure and crystallographic texture of the material in the CR and HT condition. Despite the high temperature heat treatment, the Fe40.4Ni11.3Mn34.8Al7.5Cr6 alloy retained a single phase structure indicating good phase stability. On the other hand, heat treatment caused a change in the grain structure. The CR materials exhibited an elongated grain structure whereas the HT materials had an equiaxed microstructure. The CR and HT samples were found to exhibit a weak crystallographic texture although heat treatment had caused the {111} poles to orient themselves parallel to the rolling plane whereas the CR material had a distribution of {200} poles at 45° to the rolling plane.